Post-concussion recovery in children and adolescents: A narrative review. (August 2017) - Manzanero, Silvia; Elkington, Lisa J; Praet, Stephan F; Lovell, Greg; Waddington, Gordon; Hughes, David C
Objectives: To determine if current evidence supports a slower recovery from concussion in children and adolescents when compared to adults, and to assess current management guidelines in view of this evidence. Design: Narrative review. Methods: We examined key recent research studies relating to the question "do children take longer to recover from concussion than adults?" Concussion management strategies and a sample of guidelines from different organisations were analysed in view of the current literature. Results: Recovery has been defined as return to baseline on self-reported concussion symptoms or measures of cognitive deficit. Some studies have compared measures of recovery between children and young adults, and a number of cross-sectional studies have compared groups of children of different ages. The findings varied; however, most studies suggested that children may take longer to recover than adults. Age-related differences have been considered when designing guidelines for the management of concussion. Conclusions: In view of the differences in time to recovery in children, this review supports the use of more conservative concussion management guidelines in children than in adults.